SELF-QUESTIONING IN TASK-BASED READING INSTRUCTION - Fauziyah, Nailul (Educate, 2012)
Abstract English is, in context, as the first foreign language taught in Indonesia. This has become one of a major subject in our national academic curriculum for every grade. Hence, English has been taught in all kind of disciplines and professions. And English is being taught from the early learners as pre-school students till university learners. In English foreign language teaching, reading comprehension is one of the most important factors in assessing a learner’s linguistic competence. Where the ability to read in EFL learners is acknowledged to be the most stable and durable of the second language modalities. In other words, reading plays a vital role in second language acquisition. Indeed, it is a common problem for some English teachers to understand what happens when EFL read? And what classroom activities can promote successful reading in a foreign/second language?  Then, self-questioning is the ongoing process of asking questions before, during, and after reading that are used by a reader to understand text. The questions posed are based on clues that are found in the text and are generated to spark curiosity that focuses the reader´s attention on investigating, understanding, and connecting to the text. A Self-Questioning Strategy is a set of steps that a student follows to generate, think about, predict, investigate, and answer questions that satisfy curiosity about what is being read. Thus, its strategy guides the EFL learners to achieve a successful reading of English text. Key words: Self-Questioning, Task-Based Reading Instruction.